STUDENTS' PERCEPTIONS ON THE USE OF A SMALL GROUP DISCUSSION IN IMROVING THEIR READING COMPREHENSIOM AT SMP NEGERI 1 KABARUAN - Riung, Yulivina; Liando, Nihta; Posumah, Jennie (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of this research was to find out the students’ perceptions on the use of group discussion in teaching reading. In terms of purpose, this research was a survey research. In this research, the researcher asked students’ opinions about the use of group discussion in the teaching of reading in English by using questionnaire. In terms of the nature of data, since the data collected using questionnaire were put into frequency distribution, this survey was categorized as a quantitative research. The data obtained in this study reveals that (1) 94% of the students strongly agree and agree that group discussion is interesting and effective technique that can be used to increase and motivate the respondents to engage in in reading session; (2) 79% of students strongly agree and agree that being engaged in group discussion is useful for them. They had already interested in engaging themselves in in group discussion and follow all group discussion activities; (3) 92% of the students strongly agree and agree that their engagement in group discussion is aimed at developing and improving their reading in English; and (4) 87% of the students (respondents) enjoyed being involved in group discussion in reading session and had positive perceptions toward the technique. It can then be concluded that the students positively consider group discussion an interesting, effective and useful technique for it can be used to increase their engagement, motivation and reading skills in English